2014
DOI: 10.4103/2321-3868.143623
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of wound healing in acute full-thickness skin wounds using a collagen-binding peptide with an affinity for MSCs

Abstract: Mesenchymal stem cells (MSCs) have been accepted as a promising cell source in tissue repair and regeneration. However, the inability to enrich MSCs in target areas limits their wide application. As a result, it has been a major goal to induce MSCs to be abundantly and specifically recruited to the injury site. In this study, a peptide with a specific affinity for MSCs (E7 peptide) was immobilized to a collagen scaffold via a collagen-binding domain (CBD) to construct a functional collagen scaffold. In additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…By Day 30, two of the three treatment group wounds had a wound area of 0 cm 2 , indicating complete healing. Such extensive wound surface area reduction in the treatment group compares well to trends observed by Wang, et al when characterizing a novel collagen-peptide bound synthetic scaffold in a full-thickness porcine model [ 12 ]. At 28 days, Wang, et al concluded that wounds treated with the novel bioactive scaffold exhibited a 96.9% reduction in size.…”
Section: Discussionsupporting
confidence: 77%
“…By Day 30, two of the three treatment group wounds had a wound area of 0 cm 2 , indicating complete healing. Such extensive wound surface area reduction in the treatment group compares well to trends observed by Wang, et al when characterizing a novel collagen-peptide bound synthetic scaffold in a full-thickness porcine model [ 12 ]. At 28 days, Wang, et al concluded that wounds treated with the novel bioactive scaffold exhibited a 96.9% reduction in size.…”
Section: Discussionsupporting
confidence: 77%
“…The presence of the peptide increased the efficiency of stem cell recruitment into polycaprolactone (PCL) meshes both in vitro and in vivo in a rat model in contrast to RGD peptide (Figure 1C-E). Similarly, the E7 peptide was recently combined with a collagen-binding domain and was able to enhance mesenchymal stem cell adhesion and infiltration in the collagen scaffolds in vivo in a porcine model [45] .…”
Section: Strategies To Achieve Stem and Progenitor Cell Recruitmentmentioning
confidence: 99%
“…Intensity of inflammation was significantly lower in FG group than in control group at day 7.[71]CollagenIncorporation with gold nanoparticlesCytotoxicity assay: L929 cells incubated in CS–AuX extract for 24 h; MTT cell viability assay: cell viability for all scaffold extracts was higher than 90%. Cell attachment assay: L929 fibroblasts seeded on CS–AuX for 24 h; SEM: fibroblasts on scaffolds gained their natural spindle-like shape with outstretched pseudopods spreading over the surface.CS–AuX on artificial wounds in live rat model for 14 days: milder inflammatory reaction and higher neovascularization were observed with CS–AuX than in other groups; better wound closure was observed with CS–X, CS–AuX and MatriDerm than in untreated control.[72]Modification with CBD-E7 peptide—Collagen/CBD-E7 peptide on artificial wounds in live porcine model for 28 days: significantly more MSCs were retained on CBD-E7 collagen scaffold than on pristine collagen scaffold at day 3 post-surgery; significantly rapid wound healing in collagen/CBD-E7 peptide group at days 14, 21 and 28 than in other groups; significantly higher capillary density in collagen/CBD-E7 peptide group than in other groups.[73]SSD, C 10 H 9 AgN 4 O 2 S; NHEK, normal human epidermal keratinocyte; NHEF, normal human epidermal fibroblast; HaCaT, human keratinocytes; LPS, lipopolysaccharides; Raw264.7, murine monocytes; CS–AuX, collagen-containing gold nanoparticles; MSCs, mesenchymal stem cells.…”
Section: Scaffolds From Natural Polymersmentioning
confidence: 99%